A Supramolecular Hydrogel Inspired by Elastin - 丁磊 王淑芳 武文洁 胡月晗 杨翠红 谭鸣 孔德领 杨志谋 (Chinese journal of chemistry, 2011)
Self-assembly prevails in nature and learning from nature will lead to biofunctional materials. Inspired by the protein of elastin, we reported in this study on a supramolecular hydrogel beating the elastin repeating peptide of VPGAG. The visco-elasticity property, morphology of the nanostructures, and aromatic stacking in the self-assembled nanostructure were characterized by a rheometry, transmission electron microscope （TEM）, and fluorescence microscope, respectively. The biocompatibility of the gelator was also proved by an MTT assay. Though the supramolecular hydrogel failed to exhibit a high elasticity like elastin, the thixotropic hydrogel might have potentials for the applications in fields of cell culture, controlled-drug release, etc.